(3ef CYdGe GdeMOKjf HGdMQejf GdTQjajf GdEeGe YHOGddg Hf SGde GdHUQj Gdecj (B:s (3EeGe Cgd GdMOjK HGdeSLO GdMQGe (B/s - (3GdaQjGWj, GdYQHj GdOGFQs (Beirut : Dar al-Basha'ir al-Islamiyah, 2005)
Basri,'Abd Allah ibn Salim, 1638 or 9-1721 or 2; Hadith scholars; Saudi Arabia; Mecca; biography
Keywords: al-Basri,'Abd Allah ibn Salim, -- 1638 or 9-1721 or 2; Hadith scholars -- Saudi Arabia -- Mecca -- Biography; Hadith -- Authorities